The North Makassar Straits: what lies beneath? - Hall, R.; Cloke, I.; Nur'aini, S.; Puspita, S.; Elders, Chris (The Geological Society and the European Association of Geoscientists & Engineers, 2009)
It has been accepted for many years that eastern Borneo and western Sulawesi were close together in the Late Cretaceous but the mechanism and age of formation of the Makassar Straits, which now separate them, have been the subjects of much debate. Geological studies on land show that the straits formed by Eocene rifting. However, the nature of the crust beneath the straits remains controversial. The southern parts are likely to be underlain by extended continental crust but, in the northern Makassar Straits, it is more difficult to decide. Water depths are up to 2500 m, there is a very thick sedimentary cover, the basement is not well imaged on seismic lines and there is no way of directly sampling it. Field studies from the Borneo and Sulawesi margins have provided the basis for reconstructing the development of the straits, and suggesting they are underlain by oceanic crust. The rift and its margins are asymmetrical and wide, with up to 400 km of stretched crust on the Borneo side and about 200 km on the Sulawesi side, separated by about 200 km of the deepest crust in the northern Makassar Straits. Gravity data and flexural modelling on the Borneo side suggest a junction between continental and oceanic crust beneath the Mahakam delta. The oceanic crust is inferred to be of Middle Eocene age, similar to the Celebes Sea to the north; apparent conical structures on seismic lines have been interpreted as volcanic edifices. However, the earliest backstripping studies suggested thinned continental crust in the central straits and this has been supported by interpretations of new seismic data from the offshore area west of Sulawesi. Half-graben and graben are interpreted beneath thick sediments, there are low-angle extensional faults, and lineaments crossing basement can be traced into the deepest parts of the straits. These structures suggest an origin by oblique rifting of continental crust in which the apparent conical structures are interpreted as carbonate build-ups on tilted fault blocks.